2020
DOI: 10.1186/s12902-020-00616-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of deranged thyroid function parameters in children admitted for management of diabetic ketoacidosis/diabetic ketosis

Abstract: Background: Euthyroid sick syndrome (ESS) frequently arises in children admitted with diabetic ketoacidosis/ diabetic ketosis (DKA/DK). This study evaluates the interplay of various metabolic factors with occurrence of deranged thyroid function tests in children suffering from DKA/DK. Methods: 98 DKA and 96 DK pediatric patients were selected from hospital records. Those on thyroxine replacement, with overt hypothyroidism, or with positive anti-thyroperoxidase (TPO) antibody were excluded. Tests for liver func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Our results were not inconsistent with those of Shao et al, 37 who found that in children with diabetic ketoacidosis, the NTIS group had higher levels of WBC, plasma glucose, β-hydroxybutyric acid, triglyceride, anion gap, glycosylated hemoglobin, and lower levels of prealbumin, albumin, and bicarbonate than the euthyroid group. In addition, FT3 levels were significantly correlated to β-hydroxybutyric acid, HCO3 − , anion gap, prealbumin, and glycosylated hemoglobin.…”
Section: Discussionsupporting
confidence: 59%
“…Our results were not inconsistent with those of Shao et al, 37 who found that in children with diabetic ketoacidosis, the NTIS group had higher levels of WBC, plasma glucose, β-hydroxybutyric acid, triglyceride, anion gap, glycosylated hemoglobin, and lower levels of prealbumin, albumin, and bicarbonate than the euthyroid group. In addition, FT3 levels were significantly correlated to β-hydroxybutyric acid, HCO3 − , anion gap, prealbumin, and glycosylated hemoglobin.…”
Section: Discussionsupporting
confidence: 59%
“…Many severe systemic disorders, such as heart failure, respiratory failure, renal insufficiency, and aging, can disrupt the function of the HPT axis, which is technically known as euthyroid-sick-syndrome (ESS), non-thyroid illness syndrome, because the thyroid is not directly or organically impaired. 37 Low T3 syndrome, 38 which is characterized by a lower level of T3 and an increased level of reverse T3 (rT3), 39 but an average level of TSH, is a common clinical condition. After the original condition was corrected, the ESS would decrease.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on the effect of metabolic disorders related to hyperglycemia on thyroid hormone levels in adult patients. Previous reports of pediatric cases suggested that 3-hydroxybutyrate and albumin may contribute to the development of NTI ( 7 , 9 ). In adult cases, FT3 was correlated with blood glucose level, serum osmolality, ketosis, albumin, renal function, and CRP on admission.…”
Section: Discussionmentioning
confidence: 95%
“…A study reported by Shao et al. showed that pediatric patients with DKA and DK had abnormal thyroid function and that serum FT3 levels were correlated with β-hydroxybutyrate and bicarbonate ions ( 7 ). Although it has been reported that DKA and DK are involved in the pathogenesis of NTI in pediatric cases, there has been only a few case reports of HHS complicated by NTI or systemic inflammatory response syndrome (SIRS) in adult cases.…”
Section: Introductionmentioning
confidence: 99%